Creative approach to teaching English at home reading classes at higher institutions - Dgaparova, E.C.; Bairamova, Sh.M. (Культура народов Причерноморья, 2005)
This article considers a creative approach to teaching Home Reading. It is noted that the development of communicative competence of students is achieved due to literary, stylistic analysis of Katherine Mansfield's stories, the interpretation of them, working out the scenario of some episodes from short stories. A great attention is paid to those scenes, which are suitable for playing out. While making up the scenario some elements of project work may be used what develops creative imagination and self-expression of students.